Creatine phosphokinase and urea as biochemical markers of muscle Injuries in professional football players - Osorio, J. J.; Méndez, E. A.; Aguirre-Acevedo, D.; Osorio-Ciro, J.; Calderón, J. C.; Gallo-Villegas, J. A. (Asian Journal of Sports Medicine, 2018)
Background:Although biochemical markers have been used to monitor training loads (TL), it is unknown if they can be used to predict muscle injuries (MI) in professional football (soccer) players (PFP).